(untitled) (Innovate Conferences, 2025)
This article presents a comprehensive exploration of an organizational module designed to facilitate the teaching of the subject of folk pedagogy using modular technologies in higher education. Based on a design-based research methodology, the study details the structure, implementation, and evaluation of a modular framework that enables culturally grounded, student-centered, and flexible instruction. The findings highlight improved student engagement, interdisciplinary integration, and cultural preservation achieved through localized modules, digital resources, and blended learning models. The article proposes strategic recommendations for sustainable institutionalization of modular instruction, emphasizing faculty development, regional adaptation, assessment innovation, and cross-sector collaboration. Ultimately, the organizational module emerges as a transformative model capable of bridging tradition and innovation in culturally embedded education.